Analisis Perbandingan Ideologi Bahasa Iklan Gofood dan Grabfood Melalui Analisis Wacana Kritis Fairclough - Sherly Anggreni Hasari Br Ginting; M. Surip; Syairal Fahmy Dalimunthe (Lembaga Pengembangan Kinerja Dosen, 2025)
The findings of this study reveal that the GoFood advertisement titled “Breaking News” and the GrabFood advertisement “Hematematika” serve not only as promotional tools but also as media that shape consumer mindsets and behavior. Both advertisements strategically employ language, narrative, and structure to highlight the ideas of efficiency and modernity, which align with the demands of contemporary digital society. The GoFood advertisement presents a serious narrative that emphasizes economic issues, while GrabFood adopts a humorous approach and wordplay to establish a lighter and more entertaining connection with the audience. This analysis was conducted using a descriptive qualitative approach by examining video advertisements on YouTube, with a particular focus on persuasive language and visual representation. In this sense, advertisements are understood not merely as marketing strategies, but as communicative practices embedded with ideology. Through the messages they convey, the ads promote values of efficiency, frugality, and modernity, which ultimately influence the construction of consumer identity and behavior. The study applies Norman Fairclough’s Critical Discourse Analysis framework, which consists of textual analysis, discursive practice, and socio-cultural context. This approach allows researchers to explore how language in advertisements contributes to the construction of social reality, communicates particular perspectives, and encourages audiences to respond actively.